Comb structure as a switch of resonant microwave compressor; Energy Fluxes and Radiation Effects (EFRE-2016) - Artemenko S. N. Sergey Nikolaevich; Gorev S. A. Stanislav Andreevich; Novikov S. A. Sergey Avtonomovich; Yushkov Y. G. Yuri Georgievich (2016, 2016)
Title screen